Entangled F-actin displays a unique crossover to microscale nonlinearity dominated by entanglement segment dynamics. Issue 22 (14th June 2015) - Falzone, Tobias T.; Blair, Savanna; Robertson-Anderson, Rae M.
<x xml:space="preserve">Abstract</x> We drive optically trapped microspheres through entangled F-actin at constant speeds and distances well beyond the linear regime, and measure the microscale force response of the entangled filaments during and following strain.